Avaliação da pulsação térmica para controle da poça de fusão em soldagem de raiz com MIG/MAG automatizado - Ziberov, Maksym (2013)
The Thermal Pulse GMAW process seeks the combination of relative high productivity, good weld bead finish and low spatter generation of the Pulsed GMAW with the capability of controlling welding pool of the Pulsed TIG. Nevertheless, its industrial application is still very limited, except for aluminum welding. But this GMAW version may become differential for application if a distribution of the arc/droplet heat and pressure along the joint is applied. Thus, the objective of this study was to evaluate the potential weld pool control of the Thermal Pulsed GMAW for automated welding of root passes, without backing strips. Synchronization between the thermal pulses and torch trapezoidal weaving was initially devised. In this case, the thermal pulse was applied on the joint side, ensuring to melt this region, and the thermal base applied during the transition from one side to the other, in order to minimize the possibility of weld pool collapse, by reducing the heat and pressure of arc and droplets during this period. The maximum root gap was searched by evaluating this technique under different root gaps at several oscillation amplitudes for a given combination of thermal pulse and base parameters (V-groove butt joints of carbon steel welded in flat position, with and without root face). The results showed that this approach, in contrast to the welding without any synchronization, was able to control the weld pool. Root passes with complete penetration, adequate geometry and defect free were produced for gaps ranging from 2,5 to 6 mm. The oscillation amplitude must be larger than the root gap. However, the process does not seem robust enough and requires further investigation to allow keeping the same welding parameters regardless joint geometry variations, especially in the root face and gap.